Offshoring, Endogenous Skill Decision, and Labor Market Outcomes - Pablo Agnese; Jana Hromcová (Institute for the Study of Labor (IZA), 2016)
We discuss the effects of low-skill offshoring on the endogenous schooling decision of workers along with the potential changes in the labor market. The analysis is performed in the context of a matching model with different possible equilibria. Our exercise suggests that the endogenous adjustment of low-skill workers can only partially offset the welfare-deteriorating effects of offshoring. As a result, we aim at restoring welfare by increasing the opportunity cost of staying low-skill. In addition to this, we also consider labor flexibility as an effective policy to deal with the adverse welfare effects of offshoring that befall those in the lowest end of the skill ladder.
Keywords: F66; I25; J64; 330; offshoring; welfare; skills; education; flexibility